Optimal deployment of energy-efficient ultra-dense network - Liang GE; Zhixu WANG (Dianxin kexue)
In order to maximize energy efficiency, the stochastic geometry method was used to model the uplink of a multi-cell multi-user MIMO cellular network.Then the system power consumption model was ameliorated.Based on this,an energy efficiency maximization problem with respect to base station density,transmit power,the number of base station antennas,users per cell and pilot reuse factor was obtained.Solving the problem,the optimal network deployment,as well as the relationship between the optimal variables,hardware characteristics and propagation environment was obtained.Finally, simulation and numerical results show that the ultra-dense network deployment can significantly improve the energy efficiency.However,with the further increase of the density of the base station,the improvement of the energy efficiency was quickly saturated.More interestingly,the deployment scenario determined by the energy efficiency optimization was just massive MIMO scenarios.